Computer simulation modeling and analysis of sudden load rejection in power system of Istanbul European side - (:unkn) unknown (My University, 2010)
Power quality disturbances can be occur problems in electrical power system. Severe disturbances can be result in power outages. Power system structure and size are important parameters on the effect of power quality disturbances about the possible results. In this study, the 380 kV high voltage network of Istanbul European side power system was examined. After the sudden load rejection in the power system, the network was analyzed. For the analysis, the 380 kV high voltage network of Istanbul European side power system was modeled in Matlab and the power system was simulated on the sudden load rejection. © 2010 Praise Worthy Prize S.r.l.
Keywords: Blackout; Overvoltages; Power outages; Power quality disturbances; Sudden load rejection